The negative mental health condition among different occupational group in Shaanxi province of China during the COVID-19 pandemic - Kun, Guo; Jing, Ouyang; Simin, Bai; Xiaoye, Zhang; Mingyu, Si; Youlin, Qiao; Muhamad Saliluddin, Suhainizam (Association of Cell Biology Romania, 2021)
During the COVID-19 pandemic in China, people with different backgrounds may have different negative mental health conditions. Pay attention to the negative mental health condition of the medical staff, college students, and industry workers are necessary during this period. This study is a cross-sectional study. Data was collected using the non-probability method through wenjuanxing to distribute questionnaires and the participants fill in the questionnaire online. This study found that there was no significant difference in depression condition among medical staff, college students, and industry workers in Shaanxi province (F = 0.143, P = 0.87); there was no significant difference in anxiety condition among medical staff, college students, and industry workers in Shaanxi province (F = 0.043, P = 0.96); there was no significant difference in stress condition among medical staff, college students, and industry workers in Shaanxi province (F = 1.48, P = 0.29); there was a significant difference between male and female depression condition (t = 6.1, p <0.01); there was a significant difference between male and female anxiety condition (t = 6.13, p <0.01); there was a significant difference between male and female stress condition (t = 6.07, p <0.01). According to this study found that men were more likely than women to experience depression, anxiety, and stress during the COVID-19 pandemic in China.